1998
DOI: 10.1159/000056515
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-Associated MUC1 Detected by Immunoradiometric Assays

Abstract: Fifty-four anti-MUC1 antibodies submitted to the International Society for Oncodevelopmental Biology and Medicine (ISOBM) Workshop (TD-4) were evaluated in immunoradiometric assays, using sera from carcinoma patients and healthy donors. The carcinoma serum pool contained sera from 30 patients with advanced cancer (10 breast, 10 colon, and 10 ovarian). This serum pool contained 696 kU/l MUC1, 770 µg/l CEA, and 3,700 kU/l CA 125. The reference serum pool was obtained from 10 healthy women combined with 20 sera f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This new automated assay will facilitate the rapid evaluation of new antibody combinations to MUC1 using individual patient sera rather than serum pools, and will be of considerable benefit in the analysis of the promising antibody combinations previously identified by the ISOBM MUC1 Workshop [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new automated assay will facilitate the rapid evaluation of new antibody combinations to MUC1 using individual patient sera rather than serum pools, and will be of considerable benefit in the analysis of the promising antibody combinations previously identified by the ISOBM MUC1 Workshop [13].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that some of these antibodies had specificity for carbohydrate epitopes, whereas the majority of the antibodies were directed to peptide epitopes. We tested all these antibodies in immunometric assays as both solid-phase and tracer antibodies using serum pools from cancer patients and healthy women [13]. A large number of antibody combinations were revealed as potential candidates for new promising 'cancer-specific' assays, which subsequently require testing on individual patient samples.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous workshop of the International Society for Oncodevelopmental Biology and Medicine [15], more than 50 antibodies were tested both as solid-phase and tracer antibodies [16]. Fourteen of these antibodies were considered worthwhile for further testing in immunometric assays.…”
Section: Methodsmentioning
confidence: 99%
“…The International Society for Oncodevelopmental Biology and Medicine has previously organised a workshop for the characterisation of a large panel of antibodies against MUC1, with particular emphasis on the effects of altered glycosylation [15]. The panel of antibodies were also tested in immunometric assays as both solid phase and tracer antibodies, resulting in approximately 2,500 combinations [16]. Results from this work produced 104 antibody combinations that appeared to differentiate between MUC1 in two serum pools from cancer patients and normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse monoclonal antibody MB2 was raised against MCF7/AZ cells and selected for functional inactivation of E-cadherin. 26 Mouse monoclonal anti-MUC1 (214D4 27 ) and anti-MUC5AC (21M1 22 ) antibodies, and rabbit polyclonal anti-E-cadherin antibody (␣-UMT) were a gift, respectively, from Dr. J. Hilkens (The Netherlands Cancer Institute, Amsterdam), Dr. J. Bara (INSERM U-482, Saint-Antoine Hospital, Paris, France) and Dr. J. Behrens (Friedrich-Miescher Laboratory der Max Planck society in Tübingen). The polyclonal anti-MUC5AC antibody (LUM5-1 28 ) was a gift from Dr. Carlstedt (Lund University, Sweden).…”
Section: Antibodiesmentioning
confidence: 99%